2021
DOI: 10.1016/j.ajic.2020.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Does the removal of contact precautions for MRSA and VRE infected patients change health care-associated infection rate?: A systematic review and meta-analysis

Abstract: Objective: Update existing meta-analysis to analyze if discontinuation of contact precautions (CPs) for Methicillin-resistant Staphylococcus aureus (MRSA) and Vancomycin resistant Enterococcus (VRE) colonization or infection affects hospital-associated MRSA or VRE infection rates. Methods: We conducted a systematic review of 17 studies evaluating discontinuation of CPs for MRSA and VRE. Random-effects and fixed-effects models were used to determine the pooled risk ratios (RR) of preincidence hospital-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Compared with baseline, discontinuation of contact precautions was not associated with an increase of VREfm bacteraemia incidence density in our study setting. Our findings are consistent with other studies that also did not observed an increase in VRE infection rates after contact precautions were discontinued (11,18,19). Furthermore, we did not observe significant changes to the overall VREfm cases, which includes both colonization and infection, following discontinuation of contact precautions for patients colonized or infected by VREfm in the time series analysis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared with baseline, discontinuation of contact precautions was not associated with an increase of VREfm bacteraemia incidence density in our study setting. Our findings are consistent with other studies that also did not observed an increase in VRE infection rates after contact precautions were discontinued (11,18,19). Furthermore, we did not observe significant changes to the overall VREfm cases, which includes both colonization and infection, following discontinuation of contact precautions for patients colonized or infected by VREfm in the time series analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Although some data on the impact of contact precautions for VREfm have been published, most studies focus on infection rates as a primary outcome (10,11). The effect of IPC change on nosocomial VREfm transmission events is not yet adequately investigated.…”
Section: Introductionmentioning
confidence: 99%
“…More evidence is emerging that CP do not decrease MRSA associated HAIs (5). After discontinuing CP for MRSA in 09/2015 we used an interrupted time series analysis approach to evaluate the impact of this intervention on MRSA associated HAI over close to three years.…”
Section: Discussionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention (CDC) recommends the implementation of Contact Precautions (CP) to control and prevent cross-transmission between patients with MRSA (4). However, this costly and time-consuming practice lags strong evidence (5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
See 1 more Smart Citation